REVENGE IN JEFF NATHANSON’S MOVIE SCRIPT THE LION KING - Cici Alfi Syahrin; M. Amrin Siregar (JOURNAL OF LANGUAGE, 2021)
This study discusses the revenge carried out by the protagonist in The Lion King movie script named Simba. This study aims to analyze the revenge and purpose of revenge carried out by Simba. The method used to analyze this topic is a qualitative research method, making a focus on personality of the protagonist pertaining to revenge. A revenge is an act of justice as well as injustice, depending on how a revenge is done.  This research is conducted by referring to and based on several literature reviews related to the topic and discussion carried out. The theory used to analyze the topic is put forward by Leland R. The results showed that Simba tried to take revenge because he felt he had been attacked. Besides, he wanted to restore his dignity, honour, and teach a lesson to his aggressor. Finally Simba gets what he deserves, that is he gets his rights as king in the Pride Lands.